PLACE AND ENSTRANGEMENT IN FRANZ KAFKA - Umut BALCİ (Fırat University, 2019)
One of the prominent writers of German Literature is Franz Kafka. One of the features that make him special is his style and presenting the isolating figures. Apart from this, the tie that he made between place and persons in his work is another distinguishing feauture of him. In this study, the place items of Franz Kafka’s “The Trial” will be studied and investigated how the subject of place effected the signification of the events and enstrangement of the in